Relevance Of Different Methods Of Complexing Mukhtalif Hadith In Preserving The Truth In Interpreting A Hadith - Mufid, Abdul; Makruf, Ahmad; Hidayat, Taufiq; Hidayat, Taufiq; Desy, Desy (Tasamuh: Jurnal Studi Islam, 2022)
There are a number of problems regarding the Prophet's hadiths both from method thinking and interpretation that are sometimes misleading. Of the various problems, there are some hadiths that are sometimes doubtful such as mukhtalif hadith which is considered outwardly looks contradictory. mukhtalif hadith is also one of the sources of law in Islam. Hadith is sometimes difficult to be the proposition of a charity because of the clash. But if it has gone through various processes then free from opposition then this hadith can be practiced. In the process of ikhtilaf hadith through ikhtilaf hadith whose way of settlement is clear and appropriate so that the hadith can be resolved properly, it is not arbitrary people can do the process of assurance but only people who are experts in the field of hadith and Ushul fiqh. Some of the methods used for the completion of mukhtalif hadith are tawaquf, plural, tarjih and nasakh mansukh.